Lecturer support and student academic performance: the moderating role of age - Noor Hafiza Zakariya; Hadziroh Ibrahim; Muhammad Waseem; Nurul Shahidah Ahmad Nasir (International Journal of Evaluation and Research in Education (IJERE), 2026)
Lecturer support is an important factor influencing students’ academicoutcomes in higher education. This study examines the effects of lecturersupport dimensions, accessibility and approachability (AccApp), expectationand guidance (E&G), and positive encouragement (PE) on undergraduatestudents academic performance (SAP), with age tested as a potentialmoderating variable. Using a quantitative cross-sectional design, data werecollected from 250 undergraduate students at the School of BusinessManagement, Universiti Utara Malaysia (UUM), through conveniencesampling. Data were analyzed using partial least squares structural equationmodeling (PLS-SEM) with SmartPLS 4.0. The results indicate that lecturerAccApp are positively associated with academic performance, whereasexcessive expectations and directive guidance are negatively associated. PEwas not found to have a significant direct influence. Although age exhibiteda positive direct effect on academic performance, it did not significantlymoderate the relationships between lecturer support dimensions and studentoutcomes. These findings highlight the importance of accessible andequitable E&G from lecturers to enhance academic performance inMalaysian higher education. This study contributes to a thoroughunderstanding of the factors impacting SAP and offers insights for lecturers,institutions and government to work holistically to foster an inclusiveenvironment for all parties involved. Recommendations and practicalimplications for future research are discussed.